A Framework for Design Thinking Outside the Design Profession: An Analysis of Design Thinking Implementations - Tantiyaswasdikul, Kallaya (Journal of Architectural/Planning Research and Studies (JARS), 2019)
Over the past decade, the term “design thinking” has received increasing attention in a wide range of contexts and has become increasingly familiar beyond the professional design arena. Exploration of potential cross-boundary engagements and the role of design as an agent of change for both innovation and social transformation are two main mechanisms underlying the burgeoning discussion of design thinking in areas outside the design profession. This study provides an insight into the implementation of a design-thinking approach in non-designerly contexts. To investigate how design thinking is understood and applied in relation to non-designerly thinking, an analysis was undertaken of 345 articles from the Scopus database between 2002 and 2017 that included “design thinking” as a keyword. It was found that design thinking serves as a mechanism that enables and promotes innovation and social transformation. The results show that design thinking can foster new approaches to innovation as well as complex and persistent social problems through a framework of co-creation, systemic thinking, abductive reasoning, and iteration. The findings reveal that initiatives using design-thinking approaches can deliver positive outcomes in the fields of business management, social innovation, and education.